Newborn screening for central congenital hypothyroidism: past, present and future - Mark R Garrelfs; Christiaan F Mooij; Anita Boelen; A S Paul van Trotsenburg; Nitash Zwaveling-Soonawala (European Thyroid Journal)
Congenital hypothyroidism (CH) is defined as thyroid hormone deficiency at birth and constitutes one of the most common causes of preventable intellectual disability worldwide. Central CH is caused by insufficient pituitary or hypothalamic control of thyroid function, biochemically characterized by a low serum free thyroxine (fT4), in combination with a low, normal or mildly elevated thyroid-stimulating hormone (TSH). Central CH is less common than primary CH and is part of multiple pituitary hormone deficiencies (MPHD) in most of the cases. MPHD at birth, also known as ‘congenital hypopituitarism’, is a potentially life-threatening condition due to the possible co-occurrence of adrenocorticotropin hormone and growth hormone deficiency that can result in severe hypoglycemia and adrenal crisis. To date, central CH is the only pituitary hormone deficiency suitable for newborn screening (NBS), providing an opportunity for early detection of MPHD. Even though the first NBS programs utilized T4-based methods that were able to identify central CH, most countries have since transitioned to TSH-based approaches due to the high rate of false positives associated with T4-based strategies. Now, 50 years after the introduction of NBS for CH, only a few countries around the world have a screening program capable of detecting central CH. In this paper, we review the past, present and future of NBS for central CH. We will outline the importance of early detection of central CH and discuss the challenges and opportunities of screening for this condition.